2019
DOI: 10.3390/molecules24163016
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Flavonoid Glycosides by UPLC-MS to Authenticate Commercial Lemonade

Abstract: So far, there is no report on the quality evaluation of lemonade available in the market. In this study, a sample preparation method was developed for the determination of flavonoid glycosides by ultra-performance liquid chromatography–mass spectrometry (UPLC-MS) based on vortex-assisted dispersive liquid-liquid microextraction. First, potential flavonoids in lemonade were scanned and identified by ultra-performance liquid chromatography–time of flight mass spectrometry (UPLC-TOF/MS). Five flavonoid glycosides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The determination of diosmin along with other bioflavonoids is commonly performed by chromatographic [ 10 , 11 , 12 ], spectrophotometric [ 13 , 14 , 15 ] or fluorimetric [ 16 ] methods. Electroanalytical techniques are less exploited, although they have some economic advantages and convenient characteristics such as simplicity, speed and small amount of waste.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of diosmin along with other bioflavonoids is commonly performed by chromatographic [ 10 , 11 , 12 ], spectrophotometric [ 13 , 14 , 15 ] or fluorimetric [ 16 ] methods. Electroanalytical techniques are less exploited, although they have some economic advantages and convenient characteristics such as simplicity, speed and small amount of waste.…”
Section: Introductionmentioning
confidence: 99%
“…Negative ion mode of MS E /Fast DDA has showed much more abundance daughter ions than those of the positive ion mode, and thus it was used for the structure characterization. After comparing the parent‐to‐daughter ions with in‐house database in UNIFI platform and the references [22–28], 14 flavonoids were observed and identified. Nine compounds, including rutin (Cpd 15), LQ (Cpd 16), ILQ (Cpd 25), LG (Cpd 27), quercetin (Cpd 29), ILG (Cpd 38), FM (Cpd 41), LCC (Cpd 52), and LFB (Cpd 56) were confirmed by comparing their accurate parent and daughter ions of Fast DDA spectra and retention times with those of reference compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Negative ion mode of MS E /Fast DDA has showed much more abundance daughter ions than those of the positive ion mode, and thus it was used for the structure characterization. After comparing the parent-to-daughter ions with in-house database in UNIFI platform and the references [22][23][24][25][26][27][28] . These fragmentation behaviors have showed the high similarity with those of Cpd 27, except for losing glucose moiety.…”
Section: Flavonoidsmentioning
confidence: 99%
“…The results showed that the regression equation of eriocitrin was y ¼ 523.81x À 82.61 (r ¼ 0.996), the linear range was 2.01-50.3 ng mL À1 , the intra-day precision (RSD) was 1.36%, while the inter-day precision (RSD) was 3.53% and recovery rates were 88.5%. 5 In addition, a reversed phase expressed as i pa (mA) ¼ 60.91C (mM) + 0.8447 (r ¼ 0.998) and i pa (mA) ¼ 0.864 + 0.0580c (r ¼ 0.996), respectively. Compared with the above literature, the LC-MS/MS method adopted in this experiment has high sensitivity, good linearity and feasibility, which is suitable for the pharmacokinetic study of eriocitrin.…”
Section: Methods Validationmentioning
confidence: 99%
“…Epidemiological and clinical studies show that diets with a high antioxidant capacity are closely related to signicant decreases in the plasma C-reactive protein, ischemic stroke, or the overall risk of cardiovascular disease or colorectal cancer. 1 Eriocitrin, (eriodictyol 7-O-beta-rutinoside), as the main ingredient in citrus fruits (lemon, citrus, and grapefruit), [2][3][4][5] vegetables, and processed products (drinks, wine), 6 has aroused extensive interests of the scientic community due to its strong antioxidant activity, [7][8][9] which is stronger than that of hesperidin and naringin. Modern pharmacological studies show that eriocitrin has strong lipid-lowering, anticancer and anti-inammatory activities.…”
Section: Introductionmentioning
confidence: 99%